Performance determinants of large-small business strategic alliances in South Africa - F. Ahwireng-Obeng; O. O. Egunjobi (South African Journal of Business Management, 2001)
The literature suggests that the success of strategic alliances between large and small firms is influenced by four broad factors: motivational, cultural and resource capability synergies; shared commitments, goals and roles; participative planning, operationalisation and administration; and regular open communications. This study suggests that even though mismatches and incongruencies may be evident, the alliance formation and endurance are influenced by two other factors: largely similar perceptions by both groups regarding the alliance's performance determinants; and a strong expectation by the large firm group of high future net benefits from aligning with small firms. Performance is, invariably, contingent upon implementing a number of `pre-emptive' steps during the course of the alliance.
Keywords: 650